Morphometric variation of Spicara flexuosum Rafinesque, 1810 (Teleostei: Sparidae) inhabiting the Sea of Marmara, the Aegean and the Mediterranean Coast of Türkiye - Şalcıoğlu Asli (Oceanological and Hydrobiological Studies)
In the present study, intraspecific morphometric distribution of Spicara flexuosum was investigated along the five locations on the Turkish coast based on eight morphological characters. A total of 116 samples were obtained along the Turkish coasts (Istanbul, Yalova [Armutlu], Izmir, Mersin and Antalya) by using trawlers and the handline fishing method within the period in 2014–2015. Principal component analysis and the dendrogram-based Euclidean distance method were used to evaluate different morphometric traits among five locations. The most important ratios of the morphometric loading characters were the head length to interorbital distance, head length to eye diameter, maximum body height two to head height, and head height to head length. The classification matrix based on the discriminant function analysis showed that 94.7% of original grouped were correctly classified. Principal component and cluster analysis showed the existence of two morphologically differentiated groups of S. flexuosum. First one composed of Istanbul and Yalova and the second one consisted of Izmir, Mersin and Antalya. This study is the first description of the intraspecific distribution of morphometric characters for S. flexuosum along the Turkish coast as well as the Mediterranean region for fisheries management purposes.